Comparison of breast cancer patient satisfaction with follow-up in primary care versus specialist care: results from a randomized controlled trial. - Grunfeld, E; Fitzpatrick, R; Mant, D; Yudkin, P; Adewuyi-Dalton, R; Stewart, J; Cole, D; Vessey, M (1999)
BACKGROUND: Routine follow-up of breast cancer patients in specialist clinics is standard practice in most countries. Follow-up involves regularly scheduled breast cancer check-ups during the disease-free period. The aims of follow-up are to detect breast cancer recurrence and to provide psychosocial support to the patient; however, little is known about patients' views on breast cancer follow-up. AIM: To assess the effect on patient satisfaction of transferring primary responsibility for follow-up of women with breast cancer in remission from hospital outpatient clinics to general practice. METHOD: Randomized controlled trial with 18 months' follow-up in which women received routine follow-up either in hospital outpatient clinics or from their own general practitioner. Two hundred and ninety-six women with breast cancer in remission receiving regular follow-up care at two district general hospitals in England were included in the study. Patient satisfaction was measured by means of a self-administered questionnaire supplied three times during the 18-month study period. RESULTS: The general practice group selected responses indicating greater satisfaction than did the hospital group on virtually every question. Furthermore, in the general practice group there was a significant increase in satisfaction over baseline; a similar significant increase in satisfaction over baseline was not found in the hospital group. CONCLUSION: Patients with breast cancer were more satisfied with follow-up in general practice than in hospital outpatient departments. When discussing follow-up with breast cancer patients, they should be provided with complete and accurate information about the goals, expectations, and limitations of the follow-up programme so that they can make an informed choice.